ICT Strategy Alignment Maturity for Effective IaaS Digital Transformation - Joram Kiptoo Mutai; Yonah Etene; Richard K. Ronoh (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
We argue for a more strategic approach to Infrastructure as a Service (IaaS) digital transformation, grounded in ICT strategy alignment maturity. Many organizations struggle to effectively maturely align their ICT strategies with IaaS technologies, limiting their transformation success. This research investigates the pivotal role of ICT strategy alignment maturity in driving effective IaaS adoption and transformation. A quantitative survey was conducted in two universities in Kenya, and the data were analysed using descriptive statistics, inferential tests, and regression analysis. The findings highlight that mature alignment in ICT planning significantly influences the success of IaaS digital transformation. In addition, well-established ICT governance structures and strong business-IT skills development emerged as essential enablers of both alignment maturity and transformation outcomes. This study offers empirical insights and a renewed perspective on the strategic alignment of ICT and IaaS cloud technology, contributing to both theory and practice by illustrating how alignment maturity serves as a foundation for successful digital transformation in organizations.
Keywords: ICT Strategy; Alignment Maturity; Cloud Computing; Infrastructure as a Service (IaaS); Digital Transformation